2023
DOI: 10.3390/nu15041001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Highest Level of Evidence from Randomized Controlled Trials in Omega-3 Research

Abstract: Over the years, there has been heightened interest in the health benefits of n-3 polyunsaturated fatty acids (PUFA) in reducing chronic diseases such as, cardiovascular disease (CVD), cancer, type 2 diabetes, and acute macular degeneration (AMD). Due to inconsistent findings in the evidence, a review to critically examine the plethora of evidence from randomized controlled trials (RCTs) in n-3 PUFA research was undertaken. The aim of this review is to study the highest level of evidence and to identify gaps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…Studies investigating the link between fish oil, EPA, DHA, and cancers, including colorectal carcinogenesis (CRC), have largely focused on the effects of EPA and DHA supplementation. However, the effects of EPA and DHA supplementation on cancer risk have been inconsistent (4,5). For example, while fish oil was reported to suppress CRC in various preclinical rodent studies (6)(7)(8), it was also reported to promote CRC, especially with DHAenriched formulations (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the link between fish oil, EPA, DHA, and cancers, including colorectal carcinogenesis (CRC), have largely focused on the effects of EPA and DHA supplementation. However, the effects of EPA and DHA supplementation on cancer risk have been inconsistent (4,5). For example, while fish oil was reported to suppress CRC in various preclinical rodent studies (6)(7)(8), it was also reported to promote CRC, especially with DHAenriched formulations (9,10).…”
Section: Introductionmentioning
confidence: 99%